The role of career creativities in developing identitiy and becoming expert selves - Bennett, Dawn (Routledge, 2013)
Part III of this book considers Institutional Creativities, and the current chapter considers these from the perspective of how and why to incorporate creativities that are beyond the musical. In this chapter I explore the role of career creativities in developing identity and becoming ‘expert selves’. In so doing I hope to highlight the need for music students to reorient their learning through the creative exploration of possible future lives in music: to create ‘expert selves’ that are sustainable over the career lifespan. This aim is first addressed by presenting the context, with a comparison of music students’ career purviews and the known characteristics of music careers. Then I consider academic discourses about learning, identity and work. This is followed with discussion of employability and career development. I conclude by considering the role of creativities in incorporating identity within existing programs.